Toward a Dynamic Capabilities Framework for Engendering 4IR-Enabled Circular Economy in a University of Technology - Sinxadi, Lindelwa; Ngowi, Alfred Beati; Ramakrishna, Seeram; Awuzie, Bankole (Frontiers in Sustainability, 2021)
Universities are placed in a disadvantaged position as it pertains to the holistic adoption of 4th Industrial Revolution (4IR) technologies and their subsequent deployment toward improving circular economy (CE) performance. Accordingly, literature relating to the contribution of 4IR technologies in driving effective CE implementation in higher education institution (HEI) contexts remain limited. In this study, the need for a dynamic capabilities' framework for managing the deployment of 4IR technologies toward enabling CE implementation within the context of a South African University of Technology (SAUoT), is articulated. A single case study research design was adopted for the study with SAUoT serving as the case. Qualitative data was elicited through a brainstorming session with 18 discussants from SAUoT. Thematic analysis was utilized in analyzing the data. Findings highlight the opportunities and challenges associated with the deployment of 4IR technologies in driving CE implementation within SAUoT. Also, it provided the reasons behind the inability of extant management frameworks to facilitate successful deployment of 4IR technologies for improved CE implementation in HEIs. These findings culminated in the proposal for the adoption of a dynamic capabilities-driven framework for improved strategic management in such contexts. The proposed framework presents a platform for facilitating the effective adoption and implementation of 4IR technologies for improving CE implementation performance. This study holds salient implications for the policy makers, academic leaders, and innovation managers in university ecosystems in developing country contexts.